La dimensión comunicativa en la formación del médico: una propuesta para fortalecer la relación médico-paciente. - Sánchez-Angarita, Jacinto (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2017)
The aim of this dissertation is to reflect on medical training in relation to the communicative dimension and its impact on the doctor-patient relationship. A historical approach to what is considered as medical training and its incidence on clinical practice is made in order to propose a connection between problem-based learning (PBL), the specific training of physicians in communication, and the doctorpatient relationship. This was done by recognizing the bioethical, moral, social, cultural, communicative values, among others, involved in patient care to acquire a humanized approach and depict the ethics of health care in the health sector. Based on these approaches, a proposal is made to promote education considering the PBL teaching strategy that favors training in the communicative dimension, in order to promote the integration of disciplines, the construction of meaningful learning, interdisciplinary work, and problem solving with a holistic vision. Additionally, obtaining information to solve learning situations, making decisions and finding ways of communicating with patients is intended with the purpose of strengthening the doctor-patient relationship.